Gambaran Kepercayaan Diri Mahasiswa Profesi Terhadap Perawatan Gigi Tiruan Cekat - Yenny Pragustine; Dina Lorenza (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Clinical experience and knowledge are important factors for determining clinician's confidence level in performing dental procedures. The success of fixed partial denture treatment is the accuracy of clinicians. Clinicians will undergo education to gain knowledge and practice skills in the treatment of fixed partial dentures. During education, dental students must feel confident in order to support the success of treatment so this must be based on the right method to avoid failure in the treatment of fixed partial dentures. Objectives: To know the confidence level of dental students when performing fixed partial dentures procedures. Methods: This research is a descriptive observational study with a cross-sectional study design. Results: 53.6% of respondents were included in the confidence category while for the level of knowledge included in the category of knowing 56.6% of respondents. The highly confident category was seen to have the highest scores on questions regarding the interpretation of anamnesis results in patients who want to have fixed partial dentures treatment and on the group of questions knowledge about the success of the fixed denture procedure. Conclusion: KBK19’s dental students are predominantly falls in the category of confidence and knowledgeable regarding fixed partial dentures procedures.